Positioning translation in Technical Communication Studies - Schubert, Klaus (The Journal of Specialised Translation, 2009)
In the life cycle of technical documents, translation, the object of translation studies, is only one of three major stages. A detailed analysis of the external translation process shows that many of the decisions made by a technical translator depend on a number of ‘controlling influences’. Many of these influences originate from the other two main stages, namely technical writing and documentation management. The purpose of this paper is to suggest a discipline which accounts for the entire document life cycle and to call it Technical Communication Studies.